2018
DOI: 10.1037/cou0000255
|View full text |Cite
|
Sign up to set email alerts
|

“I don’t care about you as a person”: Sexual minority women objectified.

Abstract: This study investigates sexual minority women's experiences of objectification in the United States. Data from 5 focus groups with 33 sexual minority women were analyzed using thematic analysis (Braun & Clarke, 2006, 2012). Results revealed 6 themes and 34 subthemes grouped into "manifestations of objectification: general and explicit intersections," "immediate context of relational and situational characteristics," and "broader context of oppression and privilege along gender and sexualities." First, sexual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 74 publications
3
35
0
Order By: Relevance
“…Due to an understanding of patriarchal and sexist systems, women who self-identify as feminist may be more likely to contextualize their sexual objectification experiences and less likely to internalize them via body surveillance and self-blame. Future research might replicate and extend this study's findings by focusing on sexual minority women and integrating their unique, intersectional experiences of sexual objectification (e.g., fetishized, treated as an experiment, regarded as a spectacle) and other minority stressors based on sexual orientation and gender identity (e.g., external and internalized heterosexism and bisexism; Tebbe, Moradi, Connelly, Lenzen, & Flores, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 63%
“…Due to an understanding of patriarchal and sexist systems, women who self-identify as feminist may be more likely to contextualize their sexual objectification experiences and less likely to internalize them via body surveillance and self-blame. Future research might replicate and extend this study's findings by focusing on sexual minority women and integrating their unique, intersectional experiences of sexual objectification (e.g., fetishized, treated as an experiment, regarded as a spectacle) and other minority stressors based on sexual orientation and gender identity (e.g., external and internalized heterosexism and bisexism; Tebbe, Moradi, Connelly, Lenzen, & Flores, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 63%
“…There are few in-built restrictions around data collection methods or sources in reflexive TA research. A wide range of data sources has been used in published TA research, including everything from more conventional and extensively used methods such as interviews (e.g., Robinson-Wood et al, 2020) and focus groups (e.g., Tebbe et al, 2018), to other self-report techniques such as open-ended/qualitative survey responses (e.g., Blackie et al, 2020) and solicited diaries (e.g., Schnur et al, 2009). From innovative and creative methods such as story completion (e.g., Jennings et al, 2019) and visual methods (e.g., Devine-Wright & Devine-Wright, 2009), with forms of reflexive TA specifically developed for the analysis of imagery (e.g., Gleeson, 2011), to "naturalistic" and preexisting data sources such as psychotherapy sessions (e.g., Willcox et al, 2019), online forum posts (e.g., Fletcher & StGeorge, 2011), and political speeches (e.g., Pilecki, 2017).…”
Section: Methods For Data Collectionmentioning
confidence: 99%
“…Another challenge that is experienced by women and lesbians is being objectified. Women are heavily sexualized in media, and lesbian women experience this equally, and sometimes at greater rates, than heterosexual women (Tebbe, Moradi, Connelly, Lenzen, & Flores., 2018).…”
Section: Fem Slash Fan Fiction As the Safe Space For Lesbians To Express Their Sexualitymentioning
confidence: 99%
“…Lesbian relationships have become increasingly comodified, exploited, and hyper sexualized by popular media, most often targeting male consumers' ideals of being sexually involved with two (or more) women at one time (Szymanski, Moffitt, & Carr, 2011). Studies have found that sexual minority women are primarily sexualized by men (Tebbe, Moradi, Connelly, Lenzen, & Flores., 2018). However, cyberspace is also believed to be a safe place to express one's self including minorities.…”
Section: Fem Slash Fan Fiction As the Safe Space For Lesbians To Express Their Sexualitymentioning
confidence: 99%